Kelekatan dan Kesejahteraan Psikologis Anak dan Remaja: Studi Meta-Analisis - Hepi Wahyuningsih; Resnia Novitasari; Fitri Ayu Kusumaningrum (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
The purpose of this research is to conduct a meta-analysis study on the attachment with children and adolescents’ psychological well-being. In this study, the researchers conducted a meta-analysis of eight groups. The results show that (1) the correlation effect between secure attachment and positive psychological well-being was significant; (2) the correlation effect of secure attachment with negative psychological well-being indicates a significant value; (3) the correlation effect between avoidance and positive psychological well-being was significant; (4) the correlation effect between avoidance and negative psychological well-being was significant; (5) the correlation effect between anxious and positive psychological well-being was not significant; (6) the correlation effect between anxious and negative psychological well-being was significant; (7) the correlation effect between disorganized with positive psychological well-being was significant; (8) the correlation effect between disorganized and negative psychological well-being was significant. Q values on all results indicate a high heterogeneity which indicates the presence of a moderator.